2017
DOI: 10.3390/ijms18071539
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Thermomechanical Fiber Pre-Treatment Using Twin-Screw Extrusion on the Production and Properties of Renewable Binderless Coriander Fiberboards

Abstract: The aim of this study consisted of manufacturing renewable binderless fiberboards from coriander straw and a deoiled coriander press cake, thus at the same time ensuring the valorization of crop residues and process by-products. The press cake acted as a natural binder inside the boards owing to the thermoplastic behavior of its protein fraction during thermopressing. The influence of different fiber-refining methods was evaluated and it was shown that a twin-screw extrusion treatment effectively improved fibe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0
11

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(61 citation statements)
references
References 52 publications
3
47
0
11
Order By: Relevance
“…Oils expressed using twin screw oil press are generally of better quality than those from single screw press, owing to the presence of less foreign material. A number of authors have reported higher grade oil and press cake quality from twin screw extrusion, compared to single-screw extrusion (Evon et al, 2013;Isobe et al, 1992;Uitterhaegen et al, 2015Uitterhaegen et al, , 2017.…”
Section: Pulses and Oilseedsmentioning
confidence: 99%
“…Oils expressed using twin screw oil press are generally of better quality than those from single screw press, owing to the presence of less foreign material. A number of authors have reported higher grade oil and press cake quality from twin screw extrusion, compared to single-screw extrusion (Evon et al, 2013;Isobe et al, 1992;Uitterhaegen et al, 2015Uitterhaegen et al, , 2017.…”
Section: Pulses and Oilseedsmentioning
confidence: 99%
“…Une autre possibilité d'utilisation des anas issus de la paille de lin olé agineux pourrait ê tre la fabrication de panneaux agglomé ré s de haute densité , auto-lié s par thermopressage, en sollicitant les fibres de cellulose et la lignine contenues dans les anas, respectivement comme renfort mé canique et comme liant naturel. Les co-produits provenant de la culture du tournesol et de la coriandre ont dé jà é té exploité s pour ré aliser des panneaux de haute densité par thermopressage sans ajout de ré sine supplé mentaire [10][11]. De plus, parce que les anas ré vè lent naturellement une haute teneur en lignine, celle-ci pourrait ê tre utilisé e comme liant naturel, donnant l'opportunité d'obtenir un maté riau cohé sif sans ajout de ré sine pé trosourcé e. Des panneaux agglomé ré s et auto-lié s ont dé jà é té ré alisé s avec succè s à partir de tourteaux de tournesol [10], de coriandre [11][12] ou encore de jatropha [13], grâ ce à leurs fractions proté iques agissant comme des liants naturels.…”
Section: Introductionunclassified
“…Les co-produits provenant de la culture du tournesol et de la coriandre ont dé jà é té exploité s pour ré aliser des panneaux de haute densité par thermopressage sans ajout de ré sine supplé mentaire [10][11]. De plus, parce que les anas ré vè lent naturellement une haute teneur en lignine, celle-ci pourrait ê tre utilisé e comme liant naturel, donnant l'opportunité d'obtenir un maté riau cohé sif sans ajout de ré sine pé trosourcé e. Des panneaux agglomé ré s et auto-lié s ont dé jà é té ré alisé s avec succè s à partir de tourteaux de tournesol [10], de coriandre [11][12] ou encore de jatropha [13], grâ ce à leurs fractions proté iques agissant comme des liants naturels. Pour les anas issus du lin olé agineux, il est raisonnable de supposer que les lignines contenues dans les anas pourraient agir comme liant naturel lors du thermopressage.…”
Section: Introductionunclassified
See 1 more Smart Citation
“…Theng et al (2017a) assessed boards fabricated from the rice straw that was modified by a digestion plus defibration process. Uitterhaegen et al (2017) manufactured boards from the coriander straw that was treated with a twin-screw extrusion method.…”
Section: Introductionmentioning
confidence: 99%